Implementation of A Quality Management System for Improving Work Process Efficiency in Student Activities - Betsi Rooroh; Andreas Farel Maso; Meyvi Tombeng; Fachril Amin; Christien Maria Alexandra Walangare (Publikasi Indonesia, 2026)
Background: In student organizations, effectiveness and efficiency are crucial factors to ensure the successful execution of work programs, resource management, and the achievement of organizational goals. However, various issues such as lack of coordination, delays in reporting, and inconsistencies in activity implementation still frequently occur. Therefore, the application of Quality Management System (QMS) can serve as an effective approach, providing a systematic framework for planning, implementation, monitoring, and evaluation of student activities. Objective: This study aims to investigate in greater depth the implementation of a Quality Management System (QMS) to enhance the efficiency of work processes in student activities within higher education institutions. Methods: This research uses a qualitative descriptive method through non-participatory observation, document analysis, and literature review on student organizations at a higher education institution. Results: The implementation of QMS demonstrated significant positive impacts including improved coordination, reduced administrative errors, faster decision-making, and greater adherence to schedules and work targets in student organizational activities. Conclusion: QMS implementation effectively improves work process efficiency in student activities through standardization, systematic documentation, and continuous evaluation, fostering a disciplined, transparent, and results-oriented organizational culture.